Co-occurring mental illness and substance use disorders : evidence-based integrative treatment and multicultural application - Chandler, Tricia L.; Dombrowski, Fredrick; Matthews, Tara G. (New York, NY : Routledge, 2022)
"This textbook details how mental health and addiction are interconnected through childhood trauma, how this affects neurobiology and neuropsychology, and the need for an integrated whole-person treatment for those of diverse backgrounds to enhance treatment outcomes. Using an integrative pedagogy, the book helps readers broaden their understanding of co-occurring disorders through case studies, learning objectives, key terms, quiz questions, suggested resources, and references. By linking to previous knowledge and suggesting practical applications, each chapter provides clear direction for learning more about each treatment approach, diagnosis, and population discussed within the multi-cultural and biopsychosocial perspective. Co-occurring Mental Illness and Substance Use Disorders will help graduate students in both substance use and mental health counseling make sense of integrative treatment with co-occurring disorders"--
Trauma, PTSD, substance use, & neuroscience -- Mood & anxiety disorders -- Psychotic disorders and co-occurring substance use disorders -- Co-occurring personality and substance use disorders -- Attention deficit hyperactive disorder -- Process use disorders -- Women with co-occurring disorders -- Men with co-occurring disorders -- Adolescence with co-occurring disorders -- Co-occurring disorders among the older adult population -- LGBTQIA and co-occurring disorders -- Multicultural perspectives in co-occurring treatment -- Assessment of co-occurring disorders, levels of care and ASAM requirements -- Recovery programming : 12-steps, cognitive behavioral therapy and motivational interviewing -- Biological approaches : pharmacotherapy, MAT, orthomolecular psychiatry, & nutrition -- Consciousness : spirituality, mindfulness, meditation and mindfulness-based therapies -- Creative arts & somatic therapies : psychodrama, eye movement desensitization regulation & body/mind therapies -- How East met West : the emergence of energy psychology as a body/mind approach -- Animal assisted therapies.
Keywords: Mental illness -- Treatment -- Textbooks; Substance abuse -- Treatment -- Textbooks; Psychotherapy -- Textbooks; PSYCHOLOGY / Psychopathology / Addiction